1982
DOI: 10.1002/pssa.2210710270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of symmetry of the crystalline structure on the magnetic anisotropy of Tb2Co7

Abstract: It is known that the intermetallic compounds RT2, RT3, %T7, F$Tlg, and RT5 can form in the series of the rare-earth(R) and 3d(T) metal alloys. From the structural point of view the lattices of the compounds RT3, %T,, and F$TI9 a r e combinations of elementary parts F$T4 (2RT2) and RT5 packed along the common axis at symmetry of third order: 3RT3 = F$T4 + RT5, 2 5 T 7 = F$T4+ + 2RT5, %Tlg =R2T4 + 3RT5. If the packing of parts F$T corresponds t o the hexagonal Laves phase of the MgZ% type, the structure of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…4. This observation is consistent with the report of Andreev et al [8] and Bartashevich et al [9], showing that the easy magnetization direction of Nd 2 Co 7 single crystal was along the a-axis below 225 K and along the c-axis above 290 K. In addition, the magnetization curve of Nd 2 Co 7 mimics that of NdCo 5 , implying a predominant contribution from the 1:5 slabs. The two spin-reorientation transitions are observed in the Fe substituted compounds Nd 2 Co 7−x Fe x for x < 1.5.…”
Section: Magnetic Structure and Magnetic Propertiessupporting
confidence: 94%
See 1 more Smart Citation
“…4. This observation is consistent with the report of Andreev et al [8] and Bartashevich et al [9], showing that the easy magnetization direction of Nd 2 Co 7 single crystal was along the a-axis below 225 K and along the c-axis above 290 K. In addition, the magnetization curve of Nd 2 Co 7 mimics that of NdCo 5 , implying a predominant contribution from the 1:5 slabs. The two spin-reorientation transitions are observed in the Fe substituted compounds Nd 2 Co 7−x Fe x for x < 1.5.…”
Section: Magnetic Structure and Magnetic Propertiessupporting
confidence: 94%
“…Andreev et al [8] and Bartashevich et al [9] reported that the magnetic structure of Nd 2 Co 7 experienced two fluctuations as temperature increases: a spinreorientation (SR) occurred around 225 K and another SR around 290 K, with an alteration of the easy magnetization direction (EMD) from a-axis below the first SR transition to the c-axis above the second SR transition. However, binary "R 2 Fe 7 " does not exist possibly due to much higher mixing enthalpy between R and Fe than that between R and Co [10].…”
Section: Introductionmentioning
confidence: 99%
“…4(a)), which indicates no decomposition. However, when the alloy is annealed at 1273 and 1173 K, respectively, for 15 days, part decomposition for Co 5 Tb phase was observed, as shown in Fig. 4(b) and (c), when the alloy is annealed at 1173 K for 45 days, the Co 5 Tb phase can no longer be detected in the XRD pattern ( Fig.…”
Section: The Co-tb Binary Systemmentioning
confidence: 74%
“…The Co-Tb binary system phase equilibria had also been well studied [2][3][4], with the formation of five binary compounds Co 17 Tb 2 (Zn 17 Th 2 structure type), Co 5 Tb (CaCu 5 structure type), Co 7 Tb 2 (Co 7 Er 2 structure type), Co 3 Tb (Ni 3 Pu structure type) and Co 2 Tb (Cu 2 Mg structure type) having been discovered. Specific research about the Co 5 Tb compound showed it to be present after annealing at 1273 K for 100 h [5], however, its eutectoid decomposition reaction would take place at around 1083 K [6]. Thus, ones proposed it to be a high temperature phase or a metastable phase at low temperature [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…The magnetic properties of Lu 2 Fe 14 B [1,2,9,10] and its hydride [11] have been previously investigated on polycrystalline samples. Until now no data on the preparation of Lu 2 Fe 14 B single crystals and, moreover, of its hydride have been reported.…”
Section: Introductionmentioning
confidence: 99%